Barriers and Facilitators to Provision of Influenza and Pneumococcal Vaccines in Home Health Care Agencies - Madigan, Elizabeth A. (Home Health Care Manag Pract, 2014)
The recommendations for influenza and pneumococcal vaccines are widely known yet the rates of both immunizations for home health care patients are 70 percent or less. The purpose of this study was to identify the facilitators and barriers to immunizations ultimately to improve vaccination rates among home health care patients. Using a multi-case study approach with five agencies and one group of administrators, facilitators included providing patients with a vaccine “card” and using the agency electronic medical record (EMR) for decision support/reminders. We determined that there were patient barriers (misperceptions about vaccines in general, difficulty in recalling vaccine status) and provider barriers (misperceptions about vaccines among health care workers, home health care agencies not receiving accurate information from other providers or difficulty in determining vaccine status).